Balance on older people in function of age, gender and body composition - Almeida, Sara Isabel Lebre de (2015)
Background: Falls have a high incidence in older people, representing a public health problem. They are most common in women although more mortal for men. It is known that body composition changes with aging and can predict functional and mobility problems. However, it is unknown whether the changes in the systems responsible for balance in humans are associated with age, gender or body composition. This information can contribute to understand the causes of falls and to develop prevention programs. Aim: Explore the balance-differences according to age, gender or body composition in people with 60 years or more. Methods: A quantitative cross-sectional study was conducted. The protocol included socio-demographic, anthropometric and general clinical data. Balance confidence was evaluated with the Activities-specific Balance Confidence (ABC), the balance with the Balance Evaluation System Test (BESTest) and with the Berg Balance Scale (BBS). The statistical analysis was conducted in the Statistical Package for Social Sciences (SPSS) version 22.0 for Windows. The level of significance considered was set at p<0.05. Results: 136 older people (age: 75.9±8.8) participated in this study. Balance was significantly worse with the increase of age (60-69: 86.7±15.2, 70-79: 80.7±16.1 and 80+: 72.4±15.8, p=0.001). Female presented significant worse results than male (Male: 87.0±14.5 and Female: 76.0±16.6, p=0.000). Confidence on balance was high in male and moderate in female (Male: 88.4±14.2 and Female: 76.7±24.7, p=0.033). The age group with more balance confidence was the 70 and 79 years old and the less confident was the older group +80 years old (60-69: 80.1±14.6, 70-79: 85.4±17.1 and 80+: 68.3±26.9, p=0.000). Body composition had no significant differences on balance. Conclusion: Age and gender significantly affect balance in older people and body composition does not seem to have impact on balance or balance confidence in this population. Balance confidence seems to be associated with balance in older people but not always decreases as age increases.